Keadilan Distributif Koperasi - Suroto Suroto (Jurnal Maksipreneur, 2011)
Many theories of development rely solely on growth and ignore factors of wealth distribution. It was shown of how to cope with poverty, which is often solved by good old-fashioned form of creating the job, but the question of his groundbreaking discoveries ignored, where poverty is not only concerned about employment, but also with regard to the question creatingwealth. This article mean to elaborate three models of economic system, differentiated into capitalistic model, communistic model, and cooperative model, where the cooperative model is more democratic and participatory.